2014
DOI: 10.1158/1078-0432.ccr-13-3477
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β–Regulated N-Acetyltransferase 10 Is Involved in Colorectal Cancer Invasion

Abstract: Purpose: NAT10 (N-acetyltransferase 10) is a nucleolar protein, but may show subcellular redistribution in colorectal carcinoma. In this study, we evaluated membranous staining of NAT10 in colorectal carcinoma and its clinical implications, and explored the mechanism of regulation of NAT10 redistribution.Experimental Design: The expression and subcellular redistribution of NAT10, b-catenin, E-cadherin, and GSK-3b were evaluated by immunohistochemistry in 222 cases of colorectal carcinoma. Regulation of NAT10 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…Moreover, NAT10 is highly expressed in malignant tumors (19,21), and it is essential for growth of a subtype of epithelial ovarian cancer with poor prognosis (22). Recent work demonstrated that NAT10 is the molecular target of a chemical compound called "Remodelin," which treats laminopathies, including premature aging syndromes, by correcting nuclear architecture (20).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, NAT10 is highly expressed in malignant tumors (19,21), and it is essential for growth of a subtype of epithelial ovarian cancer with poor prognosis (22). Recent work demonstrated that NAT10 is the molecular target of a chemical compound called "Remodelin," which treats laminopathies, including premature aging syndromes, by correcting nuclear architecture (20).…”
Section: Resultsmentioning
confidence: 99%
“…The salient features of this emerging class of human diseases are an increased pre-disposition to cancer and hematopoiesis and skeletons defects ( 81 ). NAT10 has been implicated in the DNA damage response, telomerase function and cytokinesis and reported as a cancer biomarker ( 31 , 34 35 ). Recently, inactivation of NAT10 has been shown to suppress morphological nuclear shape abnormalities associated with mutations in laminopathic cells, notably from patients with premature-aging progeria syndrome ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been attributed a regulatory role in telomerase function and in the DNA damage response ( 31 34 ). NAT10 is a cancer biomarker whose overexpression in various soft tissue sarcomas strikingly correlates with tumor histological grading ( 31 ) and whose subcellular distribution is a potential prognostic marker in colorectal carcinoma ( 35 ). Remarkably, NAT10 inactivation was recently shown to suppress the nuclear shape defects associated with lamin mutations in laminopathic patient cells ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…N -acetyltransferase 10 (NAT10), a member of GCN5-related N -acetyltransferases (GNAT), has been reported to be involved in the regulation of ribosome biogenesis, histone acetylation, DNA damage response, microtubule reorganization, and cell cycle progression [ 1 , 2 , 3 , 4 ]. The expression of NAT10 is reported to increase in response to DNA damage, and ectopic expression of NAT10 maintains cell survival upon DNA damage stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%